Gestational diabetes in Germany—prevalence, trend during the past decade and utilization of follow-up care: an observational study - Veronika Lappe; Gregory Gordon Greiner; Ute Linnenkamp; Anja Viehmann; Heinke Adamczewski; Matthias Kaltheuner; Dietmar Weber; Ingrid Schubert; Andrea Icks (Scientific Reports, 2023)
Abstract Gestational diabetes mellitus (GDM) is one of the most common medical complications in pregnancy. Information on key figures such as screening rates, prevalence of GDM or utilization of follow-up care and associated factors varies widely and is often lacking. The aim of our study is to provide information on screening rates for and prevalence of GDM as well as utilization of follow-up care in Germany. We used data (2010–2020) from a large, nationwide statutory health insurance containing information on inpatient and outpatient care, including diagnoses, medication and treatments. Descriptive analyses were performed to assess screening rates, prevalence of GDM and participation rates in follow-up care. A log-binomial regression model was calculated to analyze associated factors. Screening rates among pregnant women increased from 40.2% (2010) to 93.3% (2020) and prevalence from 9.4% (2010) to 15.1% (2020). The proportion of women attending follow-up care remained stable over time (around 42%). Age, educational level, insulin prescription, hypertension and obesity were positively associated with participation in follow-up care. Although over 90% of women in Germany are screened for GDM during pregnancy, follow-up care is used much less. Further research is needed to understand the trends in GDM healthcare (from screening to follow-up care) and the reasons for women's (non-)participation, as well as the attitudes and routines of the healthcare providers involved.